Critical bonding temperature for the splat bonding formation during plasma spraying of ceramic materials - Yang, Guan-Jun; Li, Cheng-Xin; Hao, Shun; Xing, Ya-Zhe; Yang, Er-Juan; Li, Chang-Jiu (Surface & coatings technology, 2013)
Controllable formation of splat bonding in thermally sprayed coatings is essential to fulfill requirements of versatile coating applications, because the bonding influences most of the coating properties. The splat bonding formation in single-layered and multi-layered Al2O3 and YSZ splats was examined at different deposition temperatures to reveal the factors dominating the splat bonding formation. Results show that the splat interface bonding was significantly influenced by the deposition temperature. There is a critical bonding temperature for the formation of the effective splat interface bonding in plasma-sprayed ceramic coating. The critical bonding temperature depends on coating materials. It is found that the critical bonding temperature is ~300°C or ~600°C for Al2O3 or YSZ, respectively. It will be shown that the critical bonding temperature concept can be used to explain qualitatively reasonably the lamellar bonding formation during multi-splats and coating deposition. •Deposition temperature significantly affects plasma-sprayed splat interface bonding.•There is a critical deposition temperature to form effective inter-splat bonding.•The critical temperature for Al2O3 and YSZ splats is 300°C and 600°C, respectively.•Bonding formation of multi-splat and coating deposition is qualitatively explained.